ChemInform Abstract: Cationic Cyclizations and Rearrangements Promoted by a Heterogeneous Gold Catalyst. Issue 27 (8th July 2014) - Vaidya, Tulaza; Cheng, Ryan; Carlsen, Peter N.; Frontier, Alison J.; Eisenberg, Richard
Abstract The catalyst is effective for different types of cationic reactions, including Nazarov cyclizations, lactonizations, and [1, 2] shifts.